The Tendency of People to Switch from Traditional Banks to PSPs Such as Revolut - Sarcanean, Grigore; Pekárek, Štěpán; Venhoda, Ondřej; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
The aim of this thesis is to critically analyze and discuss the increasingly visible trend of consumers drifting away from traditional banks to modern Payment Service Providers (PSPs) like Revolut. The study aims to explore key drivers behind this shift and encompass aspects such as convenience, affordability, innovation in technological progress, and certain regulatory changes influencing consumer requirements and desires. The hypothesis is that digitalization of financial services, along with consumer desire for flexibility and reduced fees, has been a major factor in the rising popularity of PSPs over conventional banks. This thesis contributes to the discussion of the future of banking by analyzing consumer behavior trends, regulatory evolution, and relative strengths of PSPs over traditional banks. The identification of the main drivers of this movement will be helpful in providing insight into the future of financial services and the potential pitfalls traditional banks will face in retaining customers.The theoretical part will cover literature review covering various aspects of financial technology, the transformation occurring in the banking industry and research on consumer behavior, will examine how various elements, including the cost of transactions, general user experience, the concept of financial inclusion, and the level of trust that consumers place in digital platforms, play a vital role in shaping and influencing consumer choices in the fast-evolving financial landscape of today. It will also have models that outline how traditional banking networks are shifting to decentralized financial services, how PSPs leverage technology to enhance customer satisfaction and ease of financial transactions. The empirical part will employ a survey-based model combined with a regression model to quantify the determinants of consumer adoption of PSPs compared to traditional banks.
The primary data will be collected through surveys on the use of both traditional banks and PSPs, investigating user satisfaction, accessibility of services, cost of transactions, and trust in digital financial services. The dependent variable will be the likelihood of switching to a PSP, which will be captured through survey data. Independent variables will cover service fees, transaction speed, ease of account management, customer care experience, security attitudes, and knowledge of regulations. Secondary data from industry reports, central bank statistics, and financial market trends will also be used to validate findings. An comparative analysis using both descriptive statistics and correlation analysis will be performed to identify the key trends.
Vedoucí práce: Štěpán Pekárek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses